(untitled) (American Journal of Islam and Society, 2011)
For much of the twentieth century, race and ethnicity formed the basis of Malaysian politics and, therefore, dominated its discourse. This book explores how over the past thirty years the politics of Malaysia, which was only approximately 60 percent Muslim, moved strongly in an Islamist direction, indeed, “how Islam—in particular its ideological and institutional expressions—informs the configuration of power, the nature of legitimacy, and the sources of authority in Malaysian politics and society today” (xii). To do so, Liow first examines the genesis of the Islamist agenda from the perspective of the two major political parties—the Islamist opposition Parti Islam se-Malaysia (PAS) and the dominant United Malay National Organisation (UMNO)—showing how the latter went through several changes as it evolved to place Islamism at the center of its sociopolitical agenda. He then proceeds to show how the UMNO-led government of Malaysia began to create institutions of Islamic governance, a process he terms the “bureaucratization” of Islam, which formed the basis for Prime Minister Mahathir’s claim in the 1990s that Malaysia, constitutionally a secular state, was an Islamic state. As he does so, he notes the tensions that these developments caused between the federal and state administration on the one hand and civil and religious law on the other. Liow moves on to explore the debate from the 1990s between PAS and UMNO, and within PAS itself, on how Islam might be expressed as the organizing principle for society and politics in a religiously plural Malaysia and how the non- Muslim communities responded to the parties’ endeavors ...